2017
DOI: 10.1159/000444190
|View full text |Cite
|
Sign up to set email alerts
|

How Truncating Are ‘Truncating Languages'? Evidence from Russian and German

Abstract: Russian and German have pr eviously been described as ‘truncating‘, or cutting off target frequencies of the phrase-final pitch trajectories when the time available for voicing is compromised. However, supporting evidence is rare and limited to only a few pitch categories. This paper reports a production study conducted to document pitch adjustments to linguistic materials, in which the amount of voicing available for the realization of a pitch pattern varies from relatively long to extremely short. Production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…If this analysis is correct, this would mean that the low-rising-falling melodic construction in Spanish not only has a variable nuclear accent depending on phrase length (the number of prosodic words) -a feature shared with the other two melodies presented in the previous subsection -but also that these same changes in phrase length can lead to its edge tone alternating between a very clear high target followed by a slight fall (HL% in AM notation), and a clear low target (L%). Thus, the phenomenon that we describe here differs from familiar cases of tonal crowding, in which f0 targets can be slightly displaced or undershot when under time pressure, for instance when the nuclear syllable is final in the phrase (Grabe et al 2000, Hanssen, Peters & Gussenhoven 2007, Rathcke 2016. The alternation described here between (3a) and (3b) involves alternations in the association properties of tones despite the fact that the nuclear syllable is non-final in the phrase, as both have a postnuclear unaccented syllable.…”
Section: De Du Camentioning
confidence: 78%
“…If this analysis is correct, this would mean that the low-rising-falling melodic construction in Spanish not only has a variable nuclear accent depending on phrase length (the number of prosodic words) -a feature shared with the other two melodies presented in the previous subsection -but also that these same changes in phrase length can lead to its edge tone alternating between a very clear high target followed by a slight fall (HL% in AM notation), and a clear low target (L%). Thus, the phenomenon that we describe here differs from familiar cases of tonal crowding, in which f0 targets can be slightly displaced or undershot when under time pressure, for instance when the nuclear syllable is final in the phrase (Grabe et al 2000, Hanssen, Peters & Gussenhoven 2007, Rathcke 2016. The alternation described here between (3a) and (3b) involves alternations in the association properties of tones despite the fact that the nuclear syllable is non-final in the phrase, as both have a postnuclear unaccented syllable.…”
Section: De Du Camentioning
confidence: 78%
“…Typical cases of truncation attributed to phonetic implementation have such a voiceless coda (see, e.g., Grabe 1998 for German and Grabe, Post, Nolan, and Farrar 2000 for va ri e ties of En glish). However, Rathcke (2016) has shown that patterns of truncation are languagespecific, as well as dependent on the association properties of a par tic u lar tone. Furthermore, she discusses the truncation of the fall in Rus sian rise-falls as "a categorical abandonment of an under lying boundary tone" (223).…”
Section: Tune-text Adjustmentsmentioning
confidence: 99%
“…Hence, the facilitating effect of sonority for the perception of STS could stem from aspects of sound production that also play a crucial role in pitch transmission and perception (Ladefoged & Maddieson, 1996). However, phrases consisting exclusively of sonorants do not frequently occur in natural language (Rathcke, 2017), while in singing, sonority of underlying linguistic representations is typically enhanced by lengthening of vowels, i.e., by changing timing characteristics of speech acoustics (Eckardt, 1999). A deeper understanding of STS-foundations and mechanisms will benefit from future studies into potential interactions between timbral quality of varied sentence sonority (Clements, 1990) and the phonetics of resulting pitch patterns (cf.…”
Section: The Sonority Hypothesismentioning
confidence: 99%